Evaluating the Role of Aspirin in Liver Disease: Efficacy, Safety, Potential Benefits and Risks - Amani Elshaer; Blanca C. Lizaola-Mayo (Life)
The rise in liver disease incidence and prevalence has led to increasing morbidity and mortality worldwide. Persistent hepatic inflammation drives disease progression by increasing fibrosis, advancing to cirrhosis, and potentially developing into hepatocellular carcinoma (HCC). Addressing these complications is essential to reduce liver-related mortality. Recent studies suggest that non-steroidal anti-inflammatory drugs, particularly aspirin, may play a beneficial role in managing liver disease. Aspirin’s anti-inflammatory and chemoprotective effects contribute to slowing disease progression and reducing the risks associated with chronic liver disease (CLD). This review highlights the current literature on the effects of aspirin in CLD, with a focus on patients with metabolic-associated steatotic liver disease (MASLD) and hepatitis B and C. We will examine aspirin’s potential ability to mitigate fibrosis, reduce the incidence of HCC, and lower liver-related mortality. Additionally, we will discuss its potential side effects and safety considerations, particularly in the context of liver disease, where there is an increased risk of bleeding.